2018
DOI: 10.1159/000492827
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs120963, rs152451, rs249935, rs447529, rs8053188, and rs16940342 Polymorphisms in the <b><i>PALB2</i></b> Gene and Breast Cancer Susceptibility: A Meta-Analysis

Abstract: Background: The aim of this study was to explore the association between single nucleotide polymorphisms (SNPs) in the rs120963, rs152451, rs249935, rs447529, rs8053188, and rs16940342 loci in the PALB2 gene and breast cancer risk. Methods: Studies investigating the association between SNPs in the PALB2 gene and breast cancer susceptibility were retrieved from the PubMed, Embase, Web of Science, CNKI (Chinese National Knowledge Infrastructure), WanFang, and CBM (China Biology Medicine) databases. Eligible stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
1
1
1
Order By: Relevance
“…Our results align with research study conducted in South American and Turkey population [26,42]. Furthermore a meta-analysis study also supported our result indicating non-signi cant association of rs152451 with breast cancer risk [43]. Moreover, family based study performed in Australian population signi es the potential role of (rs152451) in familial breast cancer [24].…”
Section: Discussionsupporting
confidence: 91%
“…Our results align with research study conducted in South American and Turkey population [26,42]. Furthermore a meta-analysis study also supported our result indicating non-signi cant association of rs152451 with breast cancer risk [43]. Moreover, family based study performed in Australian population signi es the potential role of (rs152451) in familial breast cancer [24].…”
Section: Discussionsupporting
confidence: 91%
“…The intronic variant rs249954 on the PALB2 gene has been found associated with the breast cancer risk in Chinese population, however has no association with breast cancer in the population under study [23]. The variant rs664677 in the DNA damage response gene ATM though not associated in our population, previously has been reported to be associated with breast cancer and lung cancer risk in Asian people [24].…”
Section: Genetic Variants Not Associated With Bc In the Population Uncontrasting
confidence: 48%
“…Along these lines, variations in tumor suppressor genes occurring in H3K4me3 domains may alter the accessibility of genes for transcription and promote cancer development and progression. Previous studies investigating PALB2 _ rs120963 have reported increased breast cancer risk associated with this variant [ 50 , 51 ]. Comparison of allele frequency that we have conducted showed statistically significant differences between the Tunisian population and those of European and African ancestries.…”
Section: Discussionmentioning
confidence: 99%